Who Writes The Articles in Spore? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Dr Peter N Vine, St Augustine, Trinidad and Tobago: /'The value of articles in SPORE continues to be limited by lack ofattribution. Knowing who wrote an article: /i) helps establish its credibility; (ii) enables readers to point out mistakes to...